2017
DOI: 10.3847/1538-4357/aa8bb6
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of Physical Parameters of White Dwarfs: A Test of the Mass–Radius Relation

Abstract: We present a detailed spectroscopic and photometric analysis of 219 DA and DB white dwarfs for which trigonometric parallax measurements are available. Our aim is to compare the physical parameters derived from the spectroscopic and photometric techniques, and then to test the theoretical mass-radius relation for white dwarfs using these results. The agreement between spectroscopic and photometric parameters is found to be excellent, especially for effective temperatures, showing that our model atmospheres and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
99
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 94 publications
(120 citation statements)
references
References 95 publications
20
99
1
Order By: Relevance
“…We presented follow-up spectroscopy of four over-luminous white dwarfs identified by Bédard, Bergeron & Fontaine (2017). Two of these, WD 0311−649 and WD 1606+422, are double-lined systems, and we provide orbital periods, mass ratios, component masses, and effective temperatures of each binary based on their spectral line profiles, spectral energy distributions, and radial velocity data.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We presented follow-up spectroscopy of four over-luminous white dwarfs identified by Bédard, Bergeron & Fontaine (2017). Two of these, WD 0311−649 and WD 1606+422, are double-lined systems, and we provide orbital periods, mass ratios, component masses, and effective temperatures of each binary based on their spectral line profiles, spectral energy distributions, and radial velocity data.…”
Section: Discussionmentioning
confidence: 99%
“…This procedure gives 4 km s −1 errors for both lines in the spectrum shown in Figure 2. Bédard, Bergeron & Fontaine (2017) showed that it is possible to constrain the atmospheric parameters (T eff and log g) of both white dwarfs in an unresolved DA+DA binary system by combining spectroscopic, photometric, and astrometric information. More specifically, they developed a deconvolution procedure that involves fitting simultaneously the observed Balmer lines and spectral energy distribution with composite model atmospheres.…”
Section: Radial Velocity Measurementsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our approach is to construct composite binary models by adding two synthetic WD spectra, properly weighted by their respective radii using the astrometric parallax constraint. We then simultaneously fit the spectroscopic Balmer line profiles and the broadband photometric measurements using the Levenberg-Marquardt algorithm (Bédard et al 2017;Kilic et al 2020). We use de-reddened GALEX FUV and NUV (Martin et al 2005), SDSS ugriz (Abolfathi et al 2018), Pan-STARRS grizy (Tonry et al 2012), and UKIDSS Y J photometry (Lawrence et al 2007).…”
Section: Joint Analysismentioning
confidence: 99%